Assessment of Warfarin Dosing Requirements After Bariatric Surgery in Patients Requiring Long‐Term Warfarin Therapy. Issue 11 (6th June 2013) - Irwin, Adriane N.; McCool, Kathleen H.; Delate, Thomas; Witt, Daniel M.
Abstract : Study Objective: To quantify the change in weekly warfarin dose after bariatric surgery in patients requiring long‐term warfarin therapy. Design: Retrospective matched‐cohort study. Setting: Anticoagulation management service in an integrated health care delivery system. Patients: Patients receiving long‐term warfarin anticoagulation who underwent bariatric surgery between January 1, 1996, and December 31, 2010 (27 patients), were matched by date of surgery (± 2 years), age (± 5 years), and target international normalized ratio (INR) range to patients receiving long‐term anticoagulation therapy who underwent other abdominal surgical procedures: cholecystectomy or endoscopic retrograde cholangiopancreatography (59 patients [control group]). Measurement and Main Results: The main end point was change in postoperative warfarin dose from baseline (preoperative dose), measured at weekly postoperative intervals from weeks 1 to 8 and again at months 3 and 6. After surgery, patients in the bariatric surgery group had statistically significant decreases in weekly warfarin doses compared with preoperative dose at all postoperative time points (week 1 dose vs preoperative dose, p<0.01; doses at all other time points vs preoperative dose, p<0.001), except at 6 months (p>0.05). No statistically significant decreases in warfarin dose were detected at any postoperative time points in the control group. Twenty patients (74.1%) in the bariatric surgery group experienced a 20% or more decrease in weekly warfarin dose compared with 19 patients (32.2%) in the control group (p=0.004). No significant differences in warfarin‐related adverse events were noted between groups. Conclusion: Weekly warfarin doses decreased in the immediate postoperative period in anticoagulated patients after bariatric surgery but returned to their preoperative doses after approximately 6 months. A similar pattern was not observed in patients in the control group who underwent other types of abdominal surgery. Compared with preoperative anticoagulation control, this resulted in reduced anticoagulation control despite close INR monitoring. If a causal relationship between bariatric surgery and warfarin sensitivity is established in future research, developing and validating a postbariatric surgery warfarin‐dosing algorithm would be valuable.